Apocalyptic urban surrealism in the city at the end of the world. (March 2023) - Wilson, Japhy
This paper responds to calls for radical experimentation in urban theory in the context of the material and psychological upheavals of Anthropocene. It does so through the development of an apocalyptic urban surrealism, based on a set of principles drawn from surrealist attempts to simulate the experience of reality characteristic of psychotic breakdown. These principles are put to work in the psychogeographical exploration of an urban resettlement scheme on the outskirts of Iquitos in the Peruvian Amazon, and the flooded informal settlement that this scheme seeks to replace. Through the relinquishment of established modes of academic sense-making, and their replacement with a surrealist interpretive delirium, alternative meanings emerge within the entrails of cannibal capitalism and the wreckage of state-regulated reality.